Practical Design Guidelines of qZSI Based Step-Up DC/DC Converter - Zakis, Janis; Vinnikov, Dmitri; Roasto, Indrek; Jalakas, Tanel (Electrical, Control and Communication Engineering, 2010)
This paper presents some design guidelines for a new voltage fed step-up DC/DC isolated converter. The most significant advantage of proposed converter is voltage buck-boost operation on single stage. The most promising application for proposed converter is in the field of distributed power generation e.g. fuel cells or photovoltaic.The most sensitive issues - such as power losses caused by high currents in the input side of converter and high transient overvoltages across the inverter bridge caused by stray inductances were discussed and solved. The proposals and recommendations to overcome these issues are given in the paper. The Selection and design guidelines of converter elements are proposed and explained.The prototype of proposed converter was built and experimentally tested. Some results are presented and evaluated.